Molecular, Subcellular and Cellular Pathogenesis Mechanisms of Tuberculous Pneumonia - V.V. Yerokhin (Саратовский научно-медицинский журнал, 2009)
Pathogenesis mechanisms of tuberculosis have been considered. It is shown, that important place in pulmonary tuberculosis therapy should belong to the means of pathogenetic therapy directed to the improvement of pulmonary circulation and living conditions of cells of lung parenchyma, restoration of local tissue immunity, including macrophage system and other defensive mechanisms, synthesis and secretion stimulation of surfactant, and use of surfactant medications.